Development Of Problem Based Learning Media On Periodic System Materials Oriented To Students’ Learning Interests - Nadia Laras Sati; Kriswantoro Kriswantoro; Febbry Romundza; Asrial Asrial; Isra Miharti; Asmiyunda Asmiyunda (SAINTIFIK@: Jurnal Pendidikan MIPA, 2026)
This research aims to produce Problem Based Learning-based learning media on the periodic system material of elements. This research is a developmental research using the Lee & Owens development model. The research instruments include interview sheets, validation questionnaires for material experts and media experts, teacher assessment questionnaires, and student response questionnaires. The product developed was validated by material experts and media experts, then assessed by teachers and tested in one-on-one trials and small group trials. The data analysis techniques used are qualitative data analysis and quantitative data analysis. The results of the study showed that the learning media based on Problem Based Learning on the periodic system material obtained a percentage of validation of material experts of 92% and media experts of 93.2% with the category of "Very Feasible". The teacher's assessment showed a percentage of 98.67% with the category "Very Feasible", while the students' response in the one-on-one trial obtained a percentage of 95% and the small group trial obtained a percentage of 96.8% with the category "Very Good". Based on these results, Problem Based Learning-based learning media is suitable for use as a chemistry learning medium and has the potential to grow students' interest in learning.